The Correlation Between Mental Health Conditions And Academic Resilience of 10th Grade Students of SMA Negeri 6 Semarang in 2023 - Waluyan, Vrimadieska Ayuanissa; Setianingsih, Eka Sari; Saptariningsih, Siti (Indonesian Journal of Guidance and Counseling: Theory and Application, 2023)
This research is motivated by the large number of students who are indicated to have mental health disorders such as experiencing anxiety, depression, self-harm, tendencies to pedophilia and tendencies to have alter egos. In addition, there are also complaints from subject teachers where most students tend not to be motivated to take part in learning and complete assignments given. This study aims to describe the correlation between mental health and academic resilience of class X students of SMA Negeri 6 Semarang. The population in this study was 432 students and a sample of 191 students was taken using simple random sampling technique. The instrument in this study was the Mental Health Inventory 38 and the psychological scale used to reveal the level of academic resilience was The Academic Resilience Scale (ARS-30). The result of a simple linear regression test is 0.000 <0.05 so that it can be concluded that mental health has an effect on academic resilience. So it can be concluded that the form of the correlation between the two variables is positive, where the higher the mental health of students, the higher their academic resilience. Conversely, if students' mental health is low, their academic resilience will also be lower. It is known that the coefficient of determination (R Square) is 0.638, which means that the influence of variable X (mental health) on variable Y (academic resilience) is 63.8%. Furthermore, if explored further using the chi square test to find out whether gender affects the level of academic resilience of students, it is found that a chi square value of 0.175 > 0.05 so from these data it can be concluded that there is no significant relationship between the level of academic resilience of students based on gender.